PENGARUH KUALITAS PRODUK, PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN VARIASI AUDIO MOBIL DI SUBUR AUDIO WORKSHOP PURWOKERTO - Akbar Rakhman; Tri Septin Muji Rahayu (Media Ekonomi, 2017)
This study aimed to analyze the effect of product quality, promotion, and price in the purchasing decision on car audio variations at consumer Subur Audioworkshop Purwokerto either partially or simultaneouslly. Methods used in sampling is sampling purposive sampling based on consideration for adjusting the criteria in order to improve the accuracy of the study sample. The analytical method used was multiple linear regression with the significant level (α) of 0,05. Results of this study showed that the quality of products significantly influence consumers' purchasing decisions, with significant value of 0,000 is less than 0,05. Variable promotion significantly influence consumers' purchasing decisions, with significant value of 0,001 is less than 0,05. Variable quality product significantly affect the purchasing decisions, with significant value of 0,000 is less than 0,05. Variable quality products, promotions and prices simultaneously influence the purchasing decisions of consumers, with a significant value of 0,000 is less than 0,05. Keywords: Quality of Product, Promotion, Price and Purchase Decision